PERUBAHAN STATUS TANAH HAK GUNA BANGUNAN MENJADI HAK MILIK DI WILAYAH HUKUM KOTA SAMARINDA BERDASARKAN UU POKOK AGRARIA - Mahrizal Maulana (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
Abstract Land has a very important role, that is to say in the Indonesian life or in the implementation of national development which was held as a continuing effort to realize a just and prosperous society based on Pancasila and the Constitution of 1945. Therefore, the setting of control, ownership and use of land needs to be more directed for further ensuring the orderly in the field of land law, land administration, land use, or maintenance of the land and the environment, so the lack of legal certainty in the land sector.Broking implementation of changes on land for residential becoming Property at the Land Office Samarinda by Minister of State for Agrarian Affairs / Head of National Land Agency Number 5 of 1998, concerning changes Broking or right to use of land for housing.Samarinda Land Office should conduct dissemination and outreach to the community in the district as well as in the interior of the change Broking into Rights Owned because besides giving legal certainty to holding the titles concerned also for the interests of the Land Office, which is an implementation Government policies in giving certainty of continuity the right to land for individual houses for Residents Indonesian country.